(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
Path loss modeling is an essential factor in radio wave propagation and equipment design. This work examined the path loss model suitable for macro cell prediction for decimetric waves (UHF waves) in Ekiti State, Nigeria. The electric field strength of the signal of the Broadcasting Service of Ekiti State (BSES Channel 41, 625.25 MHz, broadcast signal) was measured quantitatively across the state along four routes using a digital field strength meter (Dagatron TM 10) with the transmitting station as reference point. A global positioning system (GPS) hand held receiver was used to measure the geographic heights, the geographic coordinates and the line of sight of the various data points from the base station. Data obtained were used to calculate the free space path loss for all the routes using Friis equation. Whereas, Okumura-Hata models for macro cell path loss prediction were used to determine the losses along the routes. Results showed that Friis model grossly underestimated the signal losses along the routes and cannot be used to estimate losses for decimetric waves in the state. In addition, the result obtained using Okumura-Hata models for urban and sub urban were moderate and consistent. New empirical path loss models that can be used to predict channel losses and coverage areas in order to compensate for losses in the state were proposed based on Hata sub urban model. The findings of this work will enhance radio wave propagation on the UHF band and other similar channels in the study areas.